2019
DOI: 10.1037/cou0000345
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of treatment outcome in psychotherapy by patient initial symptom distress profiles.

Abstract: Understanding how different groups of patients change at different rates is important for treatment selection, planning and evaluation. This study aimed to assess whether an approach to classifying patients on the basis of initial symptom distress profiles (ISDPs) derived from a self-rated questionnaire measuring psychological distress may be useful in predicting treatment response. The Clinical Outcome in Routine Evaluation-Outcome Measure were collected from 1,095 first line mental health service patients (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
(35 reference statements)
0
5
0
1
Order By: Relevance
“…Unusual Experiences 12-items). While scaled means were utilised to minimise this (which is advocated with LPA; Uckelstam et al, 2019), high scores on variables should be interpreted as relative rather than absolute.…”
Section: Limitationsmentioning
confidence: 99%
“…Unusual Experiences 12-items). While scaled means were utilised to minimise this (which is advocated with LPA; Uckelstam et al, 2019), high scores on variables should be interpreted as relative rather than absolute.…”
Section: Limitationsmentioning
confidence: 99%
“…These findings indicate that low MP has the potential to reduce therapeutic effectiveness and to further be associated with discomfort during the therapeutic sessions. Uckelstam et al (2019) examined whether the classification of patients on the basis of their initial symptom distress profiles predicted treatment response. They found that patients with low initial distress and low deviations among problem areas fitted a profile of a very slow change rate.…”
Section: Discussionmentioning
confidence: 99%
“…A principal interest of practice-oriented psychotherapy research is to identify factors that predict treatment outcome before therapy starts [Riedel et al, 2011;Lewis et al, 2012;Uckelstam et al, 2019]. Different conceptions of success make it difficult, however, to establish universal standards for the evaluation of psychological treatment.…”
Section: Introductionmentioning
confidence: 99%